Enhancing the operational stability of unencapsulated perovskite solar cells through Cu–Ag bilayer electrode incorporation. Issue 17 (23rd April 2020) - Lin, Chieh-Ting; Ngiam, Jonathan; Xu, Bob; Chang, Yu-Han; Du, Tian; Macdonald, Thomas J.; Durrant, James R.; McLachlan, Martyn A.
Abstract : Incorporation of bilayer electrodes (Cu:Ag) significantly reduces electrode corrosion and device degradation in perovskite solar cells operating in air. A symbiosis exists whereby Ag inhibits Cu oxidation and Cu prevents interfacial reactions between the perovskite (MAPbI3 ) and Ag. Abstract : We identify a facile strategy that significantly reduces electrode corrosion and device degradation in unencapsulated perovskite solar cells (PSCs) operating in ambient air. By employing Cu–Ag bilayer top electrode PSCs, we show enhanced operational lifetime compared with devices prepared from single metal (Al, Ag and Cu) analogues. Time-of-flight secondary ion mass spectrometry depth profiles indicate that the insertion of the thin layer of Cu (10 nm) below the Ag (100 nm) electrode significantly reduces diffusion of species originating in the perovskite active layer into the electron transport layer and electrode. X-ray diffraction (XRD) analysis reveals the mutually beneficial relationship between the bilayer metals, whereby the thermally evaporated Ag inhibits Cu oxidation and the Cu prevents interfacial reactions between the perovskite and Ag. The results here not only demonstrate a simple approach to prevent the electrode and device degradation that enhance lifetime and stability but also provide insight into ageing related ion migration and structural reorganisation.